THE PROBLEM OF ENFORCEMENT IN MARRIAGE LAWS FOR A SEXUAL DIVERSITY GROUP - Wongkalasin, Prasit; Panyasai, Apisit; Prompukdee, Nattawat (Journal of Humanities, Social Sciences, and Arts, 2025)
This research article aimed to study and analyze the challenges related to the enforcement of the Marriage Equality Law in Thailand under the Civil and Commercial Code Amendment Act (No. 24), B.E. 2567 (2024). The purpose was to acknowledge the right to marriage for the LGBTQ+ community, which represents a significant step in the implementation of same-sex marriage laws. The study employed analyses based on customary law principles, natural law theory, the rule of law, and religious perspectives on same-sex marriage from Christianity and Islam to develop legal frameworks for engagement and marriage among LGBTQ+ individuals. The amendment allows same-sex couples to obtain legal rights equal to those of heterosexual couples, such as the right to inheritance, the right to adopt children, the right to marital property, the right to file for divorce, and other marriage-related legal rights. However, there are still several legal and social challenges that require careful consideration. The research findings indicated that same-sex marriage continues to face resistance from religious groups and communities that adhere to traditional values, particularly within Islam and Christianity, which do not accept same-sex marriage. Therefore, the implementation of marriage equality laws must take into account religious doctrines and prevailing social values. Although the new law acknowledges the rights of same-sex couples regarding engagement and marriage, there are still legal gaps that do not fully protect the marriage rights of LGBTQ+ individuals in certain cases. Additionally, interpretations of previous laws in court decisions reflect a lack of understanding of legal procedures and limitations associated with same-sex marriages, which are still not treated equally to heterosexual marriages. The researchers proposed that legal provisions should be expanded to allow same-sex couples to jointly and legally have children through assisted reproductive technology, thereby strengthening the concept of the family institution. Furthermore, the law should be amended to include criteria for obtaining Thai nationality through marriage for LGBTQ+ individuals.